Evaluation of Plant Growth-Promoting Rhizobacteria on chilli (Capsicum annuum L.) and brinjal (Solanum melongena L.) growth: PGPR evaluation on Brinjal and Chilli - Shyam, Dipsikha; Narzary, Diganta (Academia Journal of Biology, 2024)
This study investigates the potential of Plant Growth-Promoting Rhizobacteria (PGPR) strains, isolated from the rhizosphere of Oroxylum indicum, to enhance the growth of chilli (Capsicum annuum L.) and brinjal (Solanum melongena L.). With the increasing global demand for sustainable agricultural practices, PGPR offers an eco-friendly alternative to chemical fertilizers and pesticides. The research involved screening ten PGPR strains and their consortia for compatibility, followed by evaluating their effects on plant growth parameters, including plant height, shoot biomass, and root biomass, under controlled conditions. Statistical analysis indicated that both individual and consortia PGPR treatments significantly improved growth performance compared to untreated controls. Results demonstrated that three individual strains (Btr-7, Bcer-24, and Bcer-25) significantly enhanced plant height and biomass in chilli plants. For brinjal plants, the strains Erog-1 and Bcer-21 showed significant growth improvements when applied individually. Additionally, the use of PGPR consortia, specifically Btro-7+Bcer-13, Ptai-40+Sarl-43, Bthu-4+Bcer-24, and Bcer-24+Bcer-25, led to substantial increases in plant height and biomass for both chilli and brinjal plants. These findings highlight the potential of PGPR, both as individual strains and in consortia, to promote sustainable crop production, reducing the reliance on chemical fertilizers. Future research should focus on field trials to validate these results under diverse agro-climatic conditions and explore the commercialization potential of effective PGPR strains.